Size and PEG Length-Controlled PEGylated Monocrystalline Superparamagnetic Iron Oxide Nanocomposite for MRI Contrast Agent - Deng LH (Dove Medical Press, 2021)
Li-Hua Deng,1,2 Hai Jiang,1 Fu-Lin Lu,1 Han-Wei Wang,1 Yu Pu,1 Chang-Qiang Wu,1 Hong-Jie Tang,3 Ye Xu,4 Tian-Wu Chen,1 Jiang Zhu,1 Cheng-Yi Shen,1 Xiao-Ming Zhang1 1Medical Imaging Key Laboratory of Sichuan Province and School of Medical Imaging, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People’s Republic of China; 2Department of Radiology, First People’s Hospital of Neijiang, Neijiang 641000, People’s Republic of China; 3Department of Radiology, Nanchong Hospital of Traditional Chinese Medicine, Nanchong 637000, People’s Republic of China; 4Department of Radiology, Children’s Hospital of Chongqing Medical University, Chongqing 401122, People’s Republic of ChinaCorrespondence: Chang-Qiang Wu; Xiaoming ZhangSichuan Key Laboratory of Medical Imaging and School of Medical Imaging, Affiliated Hospital of North Sichuan Medical College, 234th Fujiang Road, Nanchong 637000, People’s Republic of ChinaTel +86-13990723836Email wucq1984@163.com; zhangxm@nsmc.edu.cnObjective: PEGylated superparamagnetic iron oxide (SPIO) is the most promising alternatives to gadolinium-based contrast agents (GBCAs) in MRI. This paper is to explore the imaging effects of PEGylated SPIO, which is influenced by particle sizes and surface polyethylene glycol (PEG) coating, using as MRI contrast agents at different magnetic field intensities.Methods: Firstly, nine PEGylated monocrystalline SPIO nanoparticles with different nanocrystal sizes and different molecular weights PEG coating were prepared, and then physical and biological properties were analyzed. Finally, MRI imaging in vivo was performed to observe the imaging performance.Results: Nine PEGylated monocrystalline SPIO nanoparticles have good relaxivities, serum stability, and biosecurity. At the same time, they show different imaging characteristics at different magnetic field intensities. Eight-nanometer SPIO@PEG5k is an effective T2 contrast agent at 3.0 T (r2/r1 = 14.0), is an ideal T1-T2 dual-mode contrast agent at 1.5 T (r2/r1 = 6.52), and is also an effective T1 contrast agent at 0.5 T (r2/r1 = 2.49), while 4-nm SPIO@PEG5k is a T1-T2 dual-mode contrast agent at 3.0 T (r2/r1 = 5.24), and is a useful T1 contrast agent at 0.5 T (r2/r1 = 1.74) and 1.5 T (r2/r1 = 2.85). MRI studies in vivo at 3.0 T further confirm that 4-nm SPIO@PEG5k displays excellent T1-T2 dual-mode contrast enhancement, whereas 8-nm SPIO@PEG5k only displays T2 contrast enhancement.Conclusion: PEGylated SPIOs with different nanocrystal sizes and PEG coating can be used as T1, T2, or T1-T2 dual-mode contrast agents to meet the clinical demands of MRI at specific magnetic fields.Keywords: magnetic resonance imaging, contrast agents, superparamagnetic iron oxide, polyethylene glycol